Stańczyk . pismo konserwatystów i liberałów, no. 6, 1987 - Gabiś, Tomasz (s.n.], 1987)
Creation and circulation: From issue no. 2=13(1990) published legally; Publication consists of sections edited separately in different regional centers. Corresponding titles listed as non-selfstanding suplements